Independent association of HLA-DPB1*02:01 with rheumatoid arthritis in Japanese populations. - Hiroshi Furukawa; Shomi Oka; Kota Shimada; Atsushi Hashimoto; Akiko Komiya; Shinichiro Tsunoda; Akiko Suda; Satoshi Ito; Koichiro Saisho; Masao Katayama; Satoshi Shinohara; Takeo Sato; et al. (PLoS ONE, 2018)
OBJECTIVE:Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized with joint destructions; environmental and genetic factors were thought to be involved in the etiology of RA. The production of anti-citrullinated peptide antibodies (ACPA) is specifically associated with RA. DRB1 is associated with the susceptibility of RA, especially ACPA-positive RA [ACPA(+)RA]. However, a few studies reported on the independent associations of DPB1 alleles with RA susceptibility. Thus, we investigated the independent association of DPB1 alleles with RA in Japanese populations. METHODS:Association analyses of DPB1 were conducted by logistic regression analysis in 1667 RA patients and 413 controls. RESULTS:In unconditioned analysis, DPB1*04:02 was nominally associated with the susceptibility of ACPA(+)RA (P = 0.0021, corrected P (Pc) = 0.0275, odds ratio [OR] 1.52, 95% confidence interval [CI] 1.16-1.99). A significant association of DPB1*02:01 with the susceptibility of ACPA(+)RA was observed, when conditioned on DRB1 (Padjusted = 0.0003, Pcadjusted = 0.0040, ORadjusted 1.47, 95%CI 1.19-1.81). DPB1*05:01 was tended to be associated with the protection against ACPA(+)RA, when conditioned on DRB1 (Padjusted = 0.0091, Pcadjusted = 0.1184, ORadjusted 0.78, 95%CI 0.65-0.94). When conditioned on DRB1, the association of DPB1*04:02 with ACPA(+)RA was disappeared. No association of DPB1 alleles with ACPA-negative RA was detected. CONCLUSION:The independent association of DPB1*02:01 with Japanese ACPA(+)RA was identified.